Toward an on-line characterization of kaolin calcination process using short-wave infrared spectroscopy - Guatame Garcia, L. A. (2020)
In the production of calcined kaolin, the on-line monitoring of the calcination reaction is becoming more relevant for the generation of optimal products. In this context, this study aimed to assess the suitability of using infrared (IR) spectroscopy as a potential technique for the on-line characterization of the calcination of kaolin. The transformation of kaolin samples calcined at different temperatures were characterized in the short-wave (SWIR) spectra using the kaolinite crystallinity (Kx) index and the depth of the water spectral feature (1900D). A high correlation between the standard operational procedure for the quality control of calcined kaolin and the Kx index was observed (r = -0.89), as well as with the 1900D parameter (r = -0.96). This study offers a new conceptual approach to the use of SWIR spectroscopy for the characterization the calcination of kaolin, withdrawing the need of using extensive laboratory techniques.